Recognizing Other Subjects : Feminist Pastoral Theology and the Challenge of Identity. - Lassiter, Katharine Eleanor, 1979- (Wipf and Stock Publishers, 2015)
How do we care justly when selves suffer because of the identities that they inhabit? Pastoral theologian Katharine Lassiter approaches this interdisciplinary question from a feminist perspective in order to understand how suffering, subject formation, and social injustice are interconnected. Reflecting on tensions in her own experiences of caring for selves, Lassiter identifies the challenges of identity in developing a pastoral theological anthropology. Drawing from theories of recognition, she argues that doing just care requires recognizing the need for recognition as well as understanding.